Clinical value of HIV-1 matched detection in patients’ blood and cerebrospinal fluid - E. V. Stepanova; O. N. Leonova; A. S. Shelomov; N. V. Fomenkova; N. E. Dementyeva; N. A. Belyakov (Журнал инфектологии)
A comparative investigation has been applied to 100 HIV infected patients with CD4 lymphocytes rate <350 cells/microliter, demanding HAART prescription, divided into two groups: 1 – without clinical features of CNS damage (54 people) and 2 – with features of CNS damage of various etiology (46 people). HIV viral load (VL) indices in blood plasma and cerebrospinal fluid (CSF) have been examined. 45,7% of damages are caused with mixed infections. CSF HIV VL level with the 2 group patients is 7,6 times as high as that of 1 group patients. HIV VL in plasma is considerably higher than in CSF. Eight patients showed increased CSF HIV VL. Brain damages of various etiology with clinical implications violate hematoencephalic barrier integrity, contribute to HIV accumulation in CSF and intensify virus replication in brain tissue. It has been concluded that CSF examination for HIV is expedient.